On the Right Tack: Reflections on Coalition-Building Initiatives acros s The Asia Foundation - Nixon, Nicola; Yates, Peter; Saluja, Sumaya; Yi, Su Lae; Lucas, Miranda; Bain, Katherine (The Asia Foundation, 2023)
Coalitions—groups of organizations and individuals that work together to pursue a common policy goal or reform—are crucial to development. S ome of The Asia Foundation’s longest-standing and most successful deve lopment programs and portfolios have used coalition-building as an imp lementation modality. This paper examines successful initiatives in Ba ngladesh, Nepal, Philippines, Sri Lanka, Thailand, and Timor-Leste. By delving into each of these, we shed light on this coalition-building modality, sharing insights about how externally supported coalitions e merge and function and contributing ideas about how such support can b e adapted to other contexts. We hope that this paper and these case st udies contribute to innovations in contemporary development theory and help practitioners use and move beyond some formulaic and technocrati c modalities, such as traditional capacity development, knowledge tran sfer, and technical assistance. People, relationships, and working par tnerships can then take center stage, and sustained cooperation will g ain primacy over short-term outputs and deliverables.